Business Model Development of a Traditional Industrial Enterprise - OREKHOVA, Svetlana V. (Journal of Advanced Research in Law and Economics, 2017)
The study is directed at the logical structure creation of the business model of Russian ferrous metallurgy enterprises. Based on the available approaches to the learning of the content and structure of the business model, its essential and necessary elements have been specified. The study’s novelty is that the object of analysis is ferrous metallurgical enterprises with low strategic flexibility, but in the conditions of market turbulence they have to change the format of their business operation. This aspect of the work is studied through the prism of the business models transformation of industrial enterprises at different life cycle stages. The authors make a conclusion that the effective changes of business architecture is possible with the positioning of an industrial enterprise as a participant of the technological platform while creating customer values. Specifying the economic essence of the technological platform made it possible to offer a basic scheme of the business model for ferrous metallurgical enterprises.